Management of non-variceal upper gastrointestinal bleeding: role of endoscopic ultrasound-guided treatments. (January 2022) - Han, Chaoqun; Ling, Xin; Liu, Jun; Lin, Rong; Ding, Zhen
Non-variceal upper gastrointestinal bleeding (NVUGIB) is a common type of upper gastrointestinal emergency with high risk of life-threatening conditions. Nowadays some standard guidelines for the treatments of NVUGIB have been established based on endoscopic therapies, including injection of glues or sclerosing agents, coiling, band ligation, and thermal therapies. Nevertheless, some patients are refractory to standard endoscopic treatments. We have noticed that endoscopic ultrasound (EUS)–guided treatments have been performed by some endoscopists in certain conditions. This review aims to evaluate the role of EUS-guided treatments in the management of NVUGIB. We performed a MEDLINE/PubMed search, and relevant studies were extracted and examined. According to the existing literature, the most common lesions were Dieulafoy's lesion, pancreatic pseudoaneurysms, and gastrointestinal stromal tumors. EUS-guided treatments mainly include injection, mechanical therapies, and combined therapies, and seem to be a promising technique in the management of NVUGIB, especially for refractory bleeding.